SYNTHESIS AND CHARACTERIZATION OF UV-CURABLE ACRYLATED URETHANE PREPOLYMERS .1. EFFECTS OF REACTIVE DILUENTS AND RELATIVE-HUMIDITY ON PHYSICAL-PROPERTIES - YILDIZ, E; GUNGOR, A; YILDIRIM, H; BAYSAL, BM (HUTHIG & WEPF VERLAG, 1994)
A UV-curable acrylated urethane prepolymer was synthesized from tolylene-2,4-diisocyanate (TDI), a polyether polyol (Arcol 1131) and endcapped with 2-hydroxyethyl methacrylate (HEMA) by addition reaction in the presence of dibutyltin dilaurate as catalyst. UV curing was performed with either diethylene glycol diacrylate or thiodiethylene glycol diacrylate as reactive diluent. The effects of reactive diluent types, their concentrations and the humidity of environment on mechanical properties of cured films were investigated. Changes in the tensile strength, elongation and Young's modulus values of the cured films upon addition of reactive diluents with different concentrations were related to the effect of the diluent on the crosslinking density of cured films. The increase of relative humidity from 50 to 95% caused a decrease of tensile strength and Young's modulus values of cured films. It is proposed that the decrease of these physical properties in high relative humidity is due to the formation of hydrogen bonding in polymer chains caused by water molecules.
Keywords: Polymer Science